The hedging capability between non-green cryptocurrency and green cryptocurrencies toward the U.S. stock market: Analysis of the effect of economic policy uncertainty - Hung, Xin Qi; Lai, Jun Hao; Khor, Seang Yi; Yap, Shun Qing (2025)
This study examines, while accounting for Economic Policy Uncertainty (EPU), the relationship between green and non-green cryptocurrencies and the US stock market. A negative correlation between the returns of green cryptocurrencies and the U.S. stock market is found in the study, which uses daily time series data from May 3, 2021, to December 31, 2024. Numerous statistical tests were performed on the data, including the GARCH model, Feasible Generalised Least Squares (FGLS), Phillips-Perron (PP) test, Augmented Dickey-Fuller (ADF) test, Jarque-Bera test, Breusch-Godfrey LM test, and ARCH LM test. The absence of a unit root has been proven by employing the ADF test and PP test. The Newey-West Heteroscedasticity and Autocorrelation Consistent (HAC) method was employed to guarantee model resilience despite the presence of heteroscedasticity, autocorrelation, and error-term’s normal distribution. According to the FGLS model, Bitcoin exhibits a positive but insignificant relationship with S&P 500 returns, whereas green cryptocurrencies have a significant negative relationship. Furthermore, whereas Bitcoin's hedging ability is unaffected by high EPU, green cryptocurrencies' hedging capacity is adversely harmed. In a nutshell, these results have important implications for future researchers, investors, and policymakers